2022
DOI: 10.3389/fgene.2022.944681
|View full text |Cite
|
Sign up to set email alerts
|

Integrative multiomics evaluation reveals the importance of pseudouridine synthases in hepatocellular carcinoma

Abstract: Background: The pseudouridine synthases (PUSs) have been reported to be associated with cancers. However, their involvement in hepatocellular carcinoma (HCC) has not been well documented. Here, we assess the roles of PUSs in HCC.Methods: RNA sequencing data of TCGA-LIHC and LIRI-JP were downloaded from the Cancer Genome Atlas (TCGA) and the International Cancer Genome Consortium (ICGC), respectively. GSE36376 gene expression microarray was downloaded from the Gene Expression Omnibus (GEO). Proteomics data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…Consistent with differential activity among pseudouridine synthases, chemotherapeutic resistance to 5-FU is often associated with increased expression of one of more pseudouridine synthases (Jin et al 2022). In hepatocellular carcinoma and colorectal cancer, higher expression of pseudouridine synthases (PUS1, PUS7, PusL1, RPUSD3, DKC1, PUS7L, PUS10, and RPUSD1) correlates with poor prognosis (Jin et al 2022; Liang et al 2022; Zhang et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with differential activity among pseudouridine synthases, chemotherapeutic resistance to 5-FU is often associated with increased expression of one of more pseudouridine synthases (Jin et al 2022). In hepatocellular carcinoma and colorectal cancer, higher expression of pseudouridine synthases (PUS1, PUS7, PusL1, RPUSD3, DKC1, PUS7L, PUS10, and RPUSD1) correlates with poor prognosis (Jin et al 2022; Liang et al 2022; Zhang et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with differential activity among pseudouridine synthases, chemotherapeutic resistance to 5-FU is often associated with increased expression of one of more pseudouridine synthases (Jin et al 2022). In hepatocellular carcinoma and colorectal cancer, higher expression of pseudouridine synthases (PUS1, PUS7, PusL1, RPUSD3, DKC1, PUS7L, PUS10, and RPUSD1) correlates with poor prognosis (Jin et al 2022; Liang et al 2022; Zhang et al 2023). Likewise, overexpression of the Dyskerin pseudouridine synthase that acts on rRNA (DKC1) predicts poor prognosis in breast cancer, while knockdown of DKC1 and Mek1/2 restricts colorectal cancer cell growth (Elsharawy et al 2020; Kan et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to the above results, we concluded that PUS1 may be a underlying diagnostic and prognostic gene for HCC, which was consistent with the result of Shi’ study. 23 We also explored the clinical application of PUS1 by joint-effect analysis, and the result manifested that patients with high PUS1 expression had a poorer prognosis when had another risk factor.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 Moreover, a study showed that some PUS enzymes play a diagnostic and prognostic role for HCC. 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation